Research Productivity Among Scholarly Communication Librarians - Christopher Hollister; Jennifer M. K. Jensen (Journal of Librarianship and Scholarly Communication, 2023)
Introduction: A growing number of academic libraries have specialized their support for scholarly communication by creating new positions or by expanding units with a focus on providing relevant services. This study was undertaken to explore the extent to which librarians with scholarly communication responsibilities produce research and scholarship, their motivations for doing so, the nature of that productivity, and the perceived impact of that activity on their professional responsibilities. Methods: The authors administered a survey of librarians who identified as having their primary job responsibilities in scholarly communication. Results: Almost all study participants produced their own scholarly work. However, a high percentage indicated that they received no relevant training in their library degree programs, and the majority experienced imposter syndrome pertaining to their own scholarship. Although most respondents were motivated to produce research by institutional expectations for promotion and tenure, greater percentages were driven by personal or professional interests. In addition, participants indicated a strong correlation between producing their own scholarship and their ability to effectively carry out their professional responsibilities. Discussion: There may be an emerging convention for scholarly communication librarianship, i.e., one that includes open education services. Findings suggest a need for scholarly communication training to be more prominent in library degree programs. They also point to the utility of making research production a job requirement, regardless of institutional expectations for professional advancement. Conclusion: The authors argue for adjustments in library education curricula and the inclusion of research production in the portfolios of scholarly communication librarians. Future research directions are proposed.